Movement of the vehicle being braked when some wheels are incapable of braking or have lost touch with the road surface - Lukoševičiene, Ona; Sokolovskij, Edgar (Transport, 2006)
Movement of the vehicle when its certain wheels have lost contact with the surface of the road or cannot be held up through other reasons is considered in the present article. The vehicle deceleration and speed which is equivalent to the corresponding length of the braking trace of the wheels when all wheels of the vehicle are being held up and when its certain wheels have lost contact with the surface of the road or cannot be held up through other reasons are ascertained. The results of the computer experiment are presented.First Published Online: 27 Oct 2010